Vocabulary Acquisition Through Expository Texts - Anita Fatimatul Laeli (ELLITE, 2016)
This paper is based on a study on students’ vocabulary acquisition after reading in the same topic. The aim of this study is to find out the effect of applying Narrow Reading on the students’ vocabulary acquisition. The data were the students’ vocabulary test results which were analyzed to see the progress after five - times treatment. The results reveal that the students’ vocabulary acquisition increased as shown by the improvement of on word knowledge in term of spelling, word meaning, part of speech and word production.Keywords: narrow reading, vocabulary acquisition, incidental learning